Climate change: the missing discourse in the Indian Parliament. (18th July 2022) - Mundoli, Seema; Jacob, Zubin; Murali, Ranjini; Nagendra, Harini
Abstract: Parliamentary questions (PQs) are a crucial oversight tool available to parliamentarians in all democracies. In a well-functioning democracy, parliamentary oversight can play an important role in climate change policy, ensuring that climate concerns are represented in national agendas. India is the largest democracy in the world and one of the countries most vulnerable to climate change. Over a 20 year period, from 1999 to 2019, we examine whether parliamentarians used PQs to address climate change issues in India. We asked four questions (a) How often are PQs raised about climate change? (b) Are vulnerable constituency interests being represented in the Parliament? (c) What kinds of questions do parliamentarians ask? and (d) Where do parliamentarians get their information on climate change from? 895 unique PQs related to climate change were raised by 1019 Ministers, forming only a fraction (∼0.3%) of the total PQs asked in parliament during this period, however the number of PQs related to climate change increased over time. PQs were not raised by the states most vulnerable to climate change, nor did they represent the concerns of socially vulnerable groups. The PQs were mostly concerned about the impacts (27.6%) and mitigation (23.4%) of climate change. Impacts on agriculture (38.3%), coastal changes (28.6%), and health (13.4%) were of main interest, along with mitigation issues related to energy (43.6%), agriculture (21.8%), and aviation (9.1%). Despite the significant and growing vulnerability of India to climate change, PQs related to climate change were largely missing. Although they have increased over time, we still find there is substantial room for growth, especially in critical areas of climate justice and adaptation relevant to the Indian context. Raising the level of parliamentary debate on climate change is critical and needs to be foregrounded.